The Impact of Accountability and Transparency on Financial Management: The Role of Internal Control Systems as a Moderating Variable at the Buleleng Regency Social Service - Budiasni, Ni Wayan Novi; Indrayani, Nyoman Nuning Surya (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study examines the role of the internal control system as a moderating variable between accountability and transparency in financial management. The analysis was conducted using a structural equation modeling (SEM) approach, specifically the Partial Least Squares (PLS) variant. Data collection involved distributing 95 surveys to employees of the Social Office in Buleleng Regency. The hypothesis testing results indicate that accountability and transparency variables have a direct, positive, and significant effect on financial management. Similarly, testing with the internal control system as a moderating variable shows its role in strengthening the relationship between accountability and transparency in financial management. Thus, the internal control system functions as a mediator between accountability and transparency variables in financial management.